1997
DOI: 10.1002/bjs.1800840408
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of different insufflation pressures for laparoscopic cholecystectomy

Abstract: Insufflation pressure significantly affects the haemodynamic changes and postoperative pain associated with laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
4
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 7 publications
7
90
4
1
Order By: Relevance
“…The greatest benefit from low-pressure techniques or abdominal lift methods is observed in patients with diseases of the cardiovascular system and the kidneys. LP pneumoperitoneum results in decreasing the adverse hemodynamic effects in comparison to standard pneumoperitoneum (12-15 mmHg) [3,19]. The present prospective randomized trial has confirmed earlier observations, also demonstrating a significant decrease in postoperative pain intensity and in the demand for analgesics in patients in whom the LP technique was employed as opposed to those in whom SP pneumoperitoneum was created.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The greatest benefit from low-pressure techniques or abdominal lift methods is observed in patients with diseases of the cardiovascular system and the kidneys. LP pneumoperitoneum results in decreasing the adverse hemodynamic effects in comparison to standard pneumoperitoneum (12-15 mmHg) [3,19]. The present prospective randomized trial has confirmed earlier observations, also demonstrating a significant decrease in postoperative pain intensity and in the demand for analgesics in patients in whom the LP technique was employed as opposed to those in whom SP pneumoperitoneum was created.…”
Section: Discussionsupporting
confidence: 79%
“…In order to minimize the adverse effects of pneumoperitoneum, the clinical practice was extended to include low-pressure pneumoperitoneum (5-7 mmHg) and the gasless technique based on abdominal integument lifting [some surgeons prefer supplementing the gasless technique with low-pressure pneumoperitoneum (4 mmHg) to achieve a better exposure of the There were no significant differences between the groups. Values are means ± SD; ASA, American Society of Anesthesiology surgical field] [3,15,19]. Although each of these techniques has its advantages and disadvantages, the rational approach seems to be to strive to employ minimum pneumoperitoneum pressure values that allow for a good exposure of the surgical field rather than to routinely employ only one technique in all patients, what has been reflected in the recommendations of EAES [12].…”
Section: Discussionmentioning
confidence: 99%
“…During CP, a decrease in cardiac stroke volume and cardiac output often has been described as well as an increase in mean arterial pressure or heart rate [2,6,9,11,17,24]. These changes are caused by an increase in the intraabdominal pressure (IAP), which is supposed to reduce venous blood return to the heart [4,7,[18][19][20] followed by a decrease in intrathoracic blood volume (ITBV) or left ventricular end diastolic volume (LVEDV) [5,14,16,25].…”
Section: Introductionmentioning
confidence: 98%
“…The mean differences in pressure were 4 mmHg in one study [136], 5 mmHg in another [6], and 7.5 mmHg in the remaining study [171]. All three studies reported a significant benefit for low-pressure CO 2 pneumoperitoneum versus conventional CO 2 pneumoperitoneum on VAS scores and for the use of supplementary analgesics.…”
Section: Warmed Co 2 Pneumoperitoneummentioning
confidence: 81%
“…From these studies and quantitative analyses, it can be concluded that low-pressure CO 2 pneumoperitoneum (<10 mmHg) has benefits over conventional pressure (>11 mmHg) [6,136,171], but that warming the gas has no analgesic benefit [121,133,145]. A gasless approach appears to have no benefit [79,168], whereas the data for the use of NO 2 [2], helium [110], humidification [102], and suction of CO 2 [62] are limited.…”
Section: Discussionmentioning
confidence: 97%